Calculation Method of Planetary Gear Train Transmission Ratio based on Adjacency Matrix - Zhao Wang; Xinping Wang; Jiexin Zhang (Jixie chuandong)
There are many types of planetary gear trains， and each one corresponds to a transmission ratio calculation formula， which makes great difficulties in the comprehensive research of planetary gear trains and the development of general design software. According to the structural diagram of the planetary gear train， the corresponding adjacency matrix is written. Then， the basic loop of the train is searched from the adjacency matrix to construct the basic loop matrix. Finally， the basic loop matrix is transformed into the coefficient matrix of the equation of motion. And use MATLAB to automate this algorithm and solve the equation of motion to obtain the gear ratio of the planetary gear train.